Trust in the network society: The social capital perspective - Chen, Jian (2010)
As the Internet becomes integrated with our daily lives, we are gradually stepping into the network society, where we could interact with people we may rarely or never meet. Moreover, the emergence of the network society suggests that the space and time are quite different from the former societies. Within the new social context, is there really any trust between persons who are not in the same place? Why should we trust those strangers online? How could we trust them? All these issues are very important for inquiry the working mechanisms of social capital in the network society. This paper try to distinguish some misunderstandings, and suggest that trust online is a real social construction, which has a great meaning for social capital in the network society.